2022
DOI: 10.2174/0929866528666211129095001
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Colistin-resistant E. coli Clinical Isolate: Explorations of the Resistome

Abstract: Background: Antimicrobial resistance is a worldwide problem after the emergence of colistin resistance since it was the last option left to treat carbapenemase-resistant bacterial infections. The mcr gene and its variants are one of the causes for colistin resistance. Besides mcr genes, some other intrinsic genes are also involved in colistin resistance but still need to be explored. Objective: The aim of this study was to investigate differential proteins expression of colistin-resistant E. coli clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Andrade et al [ 81 ] summarized the colistin action and its drug resistance mechanisms [ 81 83 ]. Recently a study explored the bunch of proteins has been involved in colistin resistance by proteomic and bioinformatics [ 33 ], which could be employed to explore future research questions in the field of colistin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Andrade et al [ 81 ] summarized the colistin action and its drug resistance mechanisms [ 81 83 ]. Recently a study explored the bunch of proteins has been involved in colistin resistance by proteomic and bioinformatics [ 33 ], which could be employed to explore future research questions in the field of colistin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria embedded in deeper layers of the bioflm seldom come into contact with antibiotics, due to the inability of these drugs to adequately penetrate into its deeper layers; this results in a 10-1000-fold higher MIC as compared to planktonic cells [35][36][37]. Most recently, our proteomics-based study on colistin-resistant E coli revealed that a panel of diferentially expressed proteins, which could be unveiled the mechanism of colistin resistance [33]. Tis study also suggested that these proteins and their pathways could be used to develop novel therapeutics against colistinresistant infections.…”
Section: Acquired Resistance Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation